Acute Cerebellitis in Children: A Many-Faceted Disease. (July 2016) - Kornreich, Liora; Shkalim-Zemer, Vered; Levinsky, Yoel; Abdallah, Wafa; Ganelin-Cohen, Esther; Straussberg, Rachel
Acute cerebellitis is a rare inflammatory condition. It may have a benign, self-limiting course or present as a fulminant disease resulting in severe cerebellar damage or even sudden death. We present the clinical, laboratory, and radiologic data in 9 children diagnosed with acute cerebellitis, who were identified by database search in our pediatric medical center from January 2000 to November 2014. The main presenting symptom was headache, and the main presenting sign was ataxia. Bilateral diffuse hemispheric involvement was the most common imaging finding at presentation. Mycoplasma pneumoniae was the most common infectious pathogen found. Treatment included steroids in all cases, antibiotics in 4, and intravenous immunoglobulins in 6. Six patients had a full recovery, and 3 had residual neurologic complications. Magnetic resonance imaging (MRI) is the modality of choice for diagnosis. The course of acute cerebellitis varies from a commonly benign and self-limiting disease to an occasionally fulminant disease, resulting in severe cerebellar damage or sudden death.